Abnormal position of lymph nodes in a freemartin sheep - Salazar PA (Dove Medical Press, 2012)
Angela M Gonella-Diaza, Luz Zoraya Duarte, Sergio Dominguez, Pedro A SalazarClínica de Grandes Animales, Facultad de Medicina Veterinaria y de Zootecnia, Universidad Cooperativa de Colombia, Bucaramanga, Santander, ColombiaAbstract: In this freemartin case report the authors present the clinical and morphological findings of a freemartin ewe with an abnormal position of two lymph nodes. Freemartins, infertile females from mixed-sex twin pregnancies, are chimeras, having two cell populations: one of their own (XX DNA) and one from their male twin (XY DNA). Freemartins can have varying degrees of phenotypic masculinization, including, in some cases, having active male gonads and exhibiting male behaviors such as heat detection and aggressiveness. During the clinical examination of the freemartin ewe, a morphological abnormality of the vulva, the presence of scrotal sacs, and a lack of mammary tissue development were noted. On inspection of the vaginal channel, an extremely enlarged clitoris, resembling a penis, was found. The clinical evidence suggested freemartinism. After the karyotyping diagnosis confirmation, a necropsy was performed and samples were taken for histology and immunohistochemistry. There were two structures found in the scrotal sacs; however, these were found to be lymph nodes, not testicles, and this was confirmed by CD3 lymph protein coloration. On histological study, the phallic structure showed corpus cavernosum and tunica albuginea. The testicles were found retained inside the abdominal cavity, with the presence of atrophic seminiferous tubules. Although the position of the testicles in freemartins has been reported as highly variable, this is the first time, to the best of the authors' knowledge, that a case has been reported where lymph nodes have been found inside the scrotal sacs. It is possible that these were the inguinal lymph nodes, trapped inside the scrotum during fetal growth and development.Keywords: freemartinism, chimera, ewe, vulva, testes